2022
DOI: 10.1186/s12889-022-13582-2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual risk and STI testing behaviour among Dutch female and male self-employed sex workers; a cross-sectional study using an Internet based survey

Abstract: Background Sex workers are men, women or transgender people who have sex in exchange for money or goods. Self-employed sex workers solicit clients independently from a third-party. Self-employed sex workers are at risk of acquiring sexually transmitted infections (STIs) through their work. We performed a cross-sectional study, using an Internet survey conducted in 2019–2020 aiming to establish sexual risk behaviour and STI testing behaviour among female and male self-employed se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(33 reference statements)
1
5
0
1
Order By: Relevance
“…In a quantitative Dutch study among self-employed sex workers, condom use was similarly to our study self-reported to be Fig. 2 Factors influencing hepatitis B vaccination behavior as reported by MSW-MSM relatively high with anal sex and low with oral sex; however, only one-third of their MSW study population (also) had sex with men (Kampman et al, 2022). Previous qualitative research among non-sex worker MSM in the USA identified physical discomfort of condoms, relationship trust, usage based on the type of sexual act, substance use, and knowledge of a partner's STI/HIV status as factors related to condom use (Giano et al, 2020).…”
Section: Literature Comparisonsupporting
confidence: 77%
“…In a quantitative Dutch study among self-employed sex workers, condom use was similarly to our study self-reported to be Fig. 2 Factors influencing hepatitis B vaccination behavior as reported by MSW-MSM relatively high with anal sex and low with oral sex; however, only one-third of their MSW study population (also) had sex with men (Kampman et al, 2022). Previous qualitative research among non-sex worker MSM in the USA identified physical discomfort of condoms, relationship trust, usage based on the type of sexual act, substance use, and knowledge of a partner's STI/HIV status as factors related to condom use (Giano et al, 2020).…”
Section: Literature Comparisonsupporting
confidence: 77%
“…Se observó que, entre las personas entrevistadas el uso del condón era inconsistente, lo que corresponde con otros estudios realizados con trabajadores y trabajadoras sexuales ( 13 ), ya que este depende de diversos factores, tanto de tipo personal de quien ofrece y de quien demanda el servicio sexual, como de aspectos sociales asociados con el trabajo sexual. En cuanto a los factores personales, estos se relacionan con el individuo con el cual se llevará a cabo la relación sexual; se evidencia que, en el caso de los clientes, el uso del condón es más frecuente con los y las trabajadoras sexuales que con sus parejas afectivo-sexuales.…”
Section: Resultsunclassified
“…Four articles examined CT- and NG-related knowledge [ 23–26 ]. A cross-sectional survey that recruited 417 FSWs in India found that knowledge of CT and NG influenced testing behaviors among FSWs.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a community randomized trial and a cross-sectional study both conducted in Peru found that FSWs who had received prevention messages in HIV/STI health education or counseling sessions in outreach programs were more likely to seek health health services including CT and NG testing [ 25 , 26 ]. A study in the Netherlands explored the determinants of reluctance to seek CT and NG testing and found that one-third of FSWs were unaware of the possibility of getting a free and anonymous test at local STI clinics [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation